Monitoring head motion in a 7T MRI scanner using an NMR field camera - Bortolotti, Laura (2022)
Magnetic Resonance Imaging (MRI) is a technique for imaging the soft tissues of the human body. Research in medical MRI is moving towards the use of ultra-high field (UHF) MRI scanners since the spatial resolution of MRI increases with the strength of the magnetic field. However, involuntary movements of the subject create artefacts that can corrupt MR images. Since high resolution images are more vulnerable to motion, this effect becomes more relevant at ultra-high field. Motion artefacts can be ameliorated if the movements of the head during the scans are tracked; this is the basis of motion correction (MoCo) techniques.